TANGGUNG JAWAB SOSIAL PERUSAHAAN - Daniri, Mas Achmad (Jurnal Legislasi Indonesia, 2009)
On April 15, 2009, The Constitutional Court Republic ofIndonesia has decided that Corporate Social Responsibilityas contained in Article 74 Law 40 year 2007 on LimitedCompany is in accordance with 1945 Constitution. Six judgesof the Constitutional Court had approved this decision whilethree judges of the Constitutional Court had expressed theirdissenting opinion. The parties who have taken this initiativeto re-examine the article were Indonesian Chamber ofCommerce and Industry (KADIN Indonesia), IndonesianBusinesswoman Association (IWAPI), Indonesian YoungEntrepreneurs Association (HIPMI) and other companies.